Efficacy of Quanduzhong capsules in regulating blood pressure circadian rhythm in essential hypertension: a multicenter, randomized, add-on controlled clinical trial - Tang, Bi-Hua; Zhou, Cong-Hui; He, Run-Ming; Li, Zi-Yun; Wang, Jin-Cheng; Cui, Yu-Ting; Zou, Jia-Xi; Xiao, Jun-Ping; Zhou, Zhi-Gang; Li, Xiao-Feng; Yang, Yan; Hu, Jing-Qing (Frontiers in Pharmacology, 2025)
BackgroundAbnormal circadian rhythm of blood pressure is recognized as an independent risk factor for target organ damage in the heart, brain, and kidneys. Eucommia ulmoides Oliv [Eucommiaceae, Eucommiae cortex], a traditional Chinese medicine, has been reported to exhibit antihypertensive effects and may regulate blood pressure variability. This study aimed to evaluate the efficacy and safety of Quanduzhong capsules in regulating the circadian rhythm of blood pressure in patients with essential hypertension.MethodsWe designed a randomized controlled clinical trial. A total of 136 participants who had essential hypertension and abnormal circadian rhythm of blood pressure were randomly assigned to the test or control group, each comprising 68 individuals, using the random number table method. Both groups maintained their original Western antihypertensive medicine regimen, with the test group receiving additional treatment of Quanduzhong capsules (administered twice daily, 1.48 g each time). The treatment duration for both groups was 12 weeks. The patients were visited at baseline and at the end of the 4th, 8th, and 12th weeks of the intervention. Their 24-h ambulatory blood pressure and clinic blood pressure were measured at baseline and the end of 12th weeks. Primary outcomes included the recovery rate of dipper blood pressure rhythm, the standard deviation of blood pressure (SD), and the coefficient of variation of blood pressure (CV).ResultsAfter 12 weeks of treatment, the results in the full analysis set and in the per-protocol set showed no statistically significant differences between the treatment group and the control group in SD and CV. However, among the subjects who did not use calcium channel blockers, the treatment group demonstrated significantly better improvements in 24-h standard deviation of diastolic blood pressure (P < 0.05) than the control group.ConclusionOur findings suggest that Quanduzhong capsules can effectively improve the circadian rhythm of blood pressure without calcium channel blockers.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=127240, identifier ChiCTR2100046830.